(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2017)
This article intends to analyze one of the most competitive economic in Portugal: the footwear cluster. Although the Portuguese economy has been affected by several economic disruptions in the last years, the footwear industry managed to remain as a competitive and resilient activity, resilient that has bet on a strategy of innovation, improvement of processes and effective communication policy in order to survive in a market characterized by an enormous competitiveness and demand. In this context, this report’s main objective is to analyze the developments in this sector critically and to check the main challenges. In methodological terms, two in-depth interviews were conducted to the APUCCAPS’s responsible beyond a qualitative analysis based on the available documents. It was verified that the footwear cluster faces significant challenges, but regardless of this fact, it has been modernized and adapted to new situations with great success.